Calcination temperature optimization, energy transfer mechanism and fluorescence temperature dependence of KLa(MoO4)2:Eu3+ phosphors. (January 2016) - Wu, Zhongli; Chen, Baojiu; Li, Xiangping; Sun, Jiashi; Zhang, Jinsu; Zhong, Hua; Zheng, Hui; Tong, Lili; Zhang, Xiangqing; Xia, Haiping
Abstract: The optimum calcination temperature for KLa(MoO4 )2 :Eu 3+ phosphor was confirmed to be 1000 °C via checking the XRD patterns, SEM images and fluorescence spectra for the samples derived from solid state reaction. The energy transfer behavior between Eu 3+ ions was studied. It was found that electric dipole–dipole interaction is responsible for the fluorescence quenching of 5 D2 and 5 D1 levels, but exchange interaction is in charge of 5 D0 fluorescence quenching. It was also observed that color coordinates of the studied phosphor can be tuned when the doping concentration is relatively low. The fluorescence thermal quenching process was investigated. It was found the thermal quenching followed well crossover model. Judd–Ofelt parameters of Eu 3+ in KLa(MoO4 )2 were obtained, and the optical transition properties were further discussed. Highlights: Optimum calcination temperature for preparing KLa(MoO4 )2 :Eu 3+ phosphors was confirmed. Concentration quenching mechanisms for Eu 3+ fluorescence were investigated. Optical transition properties of Eu 3+ in KLa(MoO4 )2 host were studied. Temperature effect of red emission of KLa(MoO4 )2 :Eu 3+ phosphor was analyzed.